2018
DOI: 10.29278/azd.476349
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light on biosynthesis of alkamide, caffeic acid derivatives and echinacoside in Echinacea purpurea L. callus cultures

Abstract: Light is not only effective in photosynthesis, growth and development, but also play an important role in biosynthesis of primary and secondary metabolites. The present research was aimed to determine effect of light on biosynthesis of alkamide, caffeic acid derivatives and echinacoside in cell suspension cultures of Echinacea purpurea L. Stem explants derived from sterile plants were subjected to callus culture in a B5 media supplemented with 1.0 mg/L BAP and 2.0 mg/L NAA. Afterward, 8-day cell cultures were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…For instance, Bandhakavi and Kamarapu (2016) reported that when 2% (v/v) YE was treated with cell cultures, it produced 19 mgl − 1 oleanolic acid. Also, in Echinacea purpurea, the alkamide content raised from 24.2 µgg − 1 to 57.7 µgg − 1 (1.33 fold increase) with the application of 50 mgl − 1 YE (Acikgoz et al 2018) thus substantiating the elevated synthesis of alkamides especially spilanthol in A. ciliata as observed here.…”
Section: Elicitation Of Cell Suspension Culturessupporting
confidence: 86%
See 1 more Smart Citation
“…For instance, Bandhakavi and Kamarapu (2016) reported that when 2% (v/v) YE was treated with cell cultures, it produced 19 mgl − 1 oleanolic acid. Also, in Echinacea purpurea, the alkamide content raised from 24.2 µgg − 1 to 57.7 µgg − 1 (1.33 fold increase) with the application of 50 mgl − 1 YE (Acikgoz et al 2018) thus substantiating the elevated synthesis of alkamides especially spilanthol in A. ciliata as observed here.…”
Section: Elicitation Of Cell Suspension Culturessupporting
confidence: 86%
“…In A. ciliata, upon chitosan treatment, maximum amount of spilanthol (4696.337 µgg − 1 ) was noticed at 25 mgl − 1 chitosan for 72 hours exposure time. In previous studies chitosan elicitation enhanced the production of alkamides in Echinacea purpurea hairy root cultures and cell suspension cultures (Romeiro et al 2009;Acikgoz et al 2018). However, with YE, maximum 6011.431 µgg − 1 spilanthol was observed in 24 hours exposure in 0.5% YE augmented medium, after which it dropped to 4345.010 µgg − 1 and then to 3483.945µgg − 1 after 72 hours exposure.…”
Section: Elicitation Of Cell Suspension Culturesmentioning
confidence: 89%
“…Classical plant production methods and the extraction of secondary metabolites prove more resource-intensive and time-consuming compared to cell cultures. Hence, tissue culture techniques, particularly callus culture, emerge as popular methods for secondary metabolite production (Açıkgöz et al, 2018a;Açıkgöz et al, 2018b;Açıkgöz et al, 2022;Dağlioğlu et al, 2022;Ebru et al, 2022;Açıkgöz et al, 2023). Callus culture efficiently generates products of specific quality and standards, enhances genetic diversity, introduces new compounds absent in the mother plant, optimizes space utilization, and utilizes minimal resources.…”
Section: Introductionmentioning
confidence: 99%